2021
DOI: 10.3390/life11010024
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Two-Sample Mendelian Randomization Analysis Identifies Shared Genetic Origin of Endometriosis and Associated Phenotypes

Abstract: Endometriosis, one of the most common gynecological disorders, is a complex disease characterized by the growth of endometrial-like tissue in extra-uterine locations and is a cause of pelvic pain and infertility. Evidence from observational studies indicate that endometriosis usually appears together with several other phenotypes. These include a list of autoimmune diseases, most of them more prevalent in women, anthropometric traits associated with leanness in the adulthood, as well as female reproductive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…BMI is substantially and significantly lower in women with endometriosis compared with controls (Aarestrup et al, 2020; Backonja et al, 2017; Garitazelaia et al, 2021; Rossi et al, 2021; Shah et al, 2013); and by meta-analyses in Liu and Zhang (2017), Yong and Weiyuan (2017) and Jenabi et al (2019). For example, one study found that women with the most severe stage of endometriosis had the lowest BMI, although the overall relationship between disease severity and BMI was non-linear (Byun et al, 2020).…”
Section: Sexual Selection Of Endometriosismentioning
confidence: 99%
“…BMI is substantially and significantly lower in women with endometriosis compared with controls (Aarestrup et al, 2020; Backonja et al, 2017; Garitazelaia et al, 2021; Rossi et al, 2021; Shah et al, 2013); and by meta-analyses in Liu and Zhang (2017), Yong and Weiyuan (2017) and Jenabi et al (2019). For example, one study found that women with the most severe stage of endometriosis had the lowest BMI, although the overall relationship between disease severity and BMI was non-linear (Byun et al, 2020).…”
Section: Sexual Selection Of Endometriosismentioning
confidence: 99%
“…It is therefore of note that Rahmioglu and colleagues have reported a significant enrichment of common SNPs when comparing datasets based on fat distribution and endometriosis (Rahmioglu et al, 2015) including shared genes associated with the WNT signalling pathway (Table 3). A recent analysis using two-sample randomization analysis also found evidence that reduced body weight/BMI and variants that expose women to more episodes of menstruation might be mediating genetic susceptibility to endometriosis (Garitazelaia et al, 2021) which backs up epidemiological and other genetic data including GWAS discussed above.…”
Section: Genomic Studies Have Revealed Links Between Endometriosis Reproductive Traits and Other Disordersmentioning
confidence: 80%
“…These analyses have shown that endometriosis shares causal genetic risk factors with early menarche, shorter menstrual cycles, lower WHR, lower BMI, and lower levels of AMH. 38 As described above, lower AMH is independently associated with a shorter AGD among women (without endometriosis or PCOS) undergoing in vitro fertilization 22 ; AMH levels are also positively correlated with serum testosterone among reproductive-age women, 39 , 40 and BMI is positively associated with serum testosterone among premenopausal women without reproductive disorders. 41 , 42 Taken together with the data on AGD, these findings provide evidence that low testosterone and its correlates are involved in the genetic and developmental basis of endometriosis.…”
Section: Reduced Androgen Levels As Outcomes Of Genetic and Epigeneti...mentioning
confidence: 86%